Switching nuclearity and Co(II) content through stoichiometry adjustment: Co II 6 Co III 3 and Co II Co 4 III mixed valent complexes and a study of their magnetic properties - Funes, Víctor Alejandro (2015)
We are reporting two new mixed valent Co(ii)/Co(iii) polynuclear complexes, Co II 6 Co III 3 and Co II Co III 4 , bearing different amount of Co(ii) ions in their cores, through the employment of the multidentate triethanolamine (teaH 3 ) ligand in different stoichiometric ratios. We present a complete picture of the magnetic behaviour of both complexes through a combined usage of the susceptibility, magnetization and X-band EPR data as well as broken-symmetry DFT calculations. Compound 1 shows an atypical spin-only behaviour, probably due to the presence of four and five coordinated Co(ii) sites as well as highly distorted six coordinated Co(ii) ions, promoting a high degree of orbital contribution quenching. Through the usage of a simplified exchange coupling scheme and relying on DFT based magneto-structural correlation we have been able to explain the observed diamagnetic ground state. Concerning compound 2, DC magnetic data supported by X-band EPR measurements suggest the existence of anisotropy with a zero-field splitting parameter D, at least in the range of 2-10 cm -1 . In agreement with this description, a slow relaxation of magnetization is observed after applying a small external magnetic field, under AC measurements. Field and temperature dependence of the characteristic relaxation time establishes a thermal barrier for magnetization reversal of about 25 cm -1 , which is in good agreement with the energy splitting of the |±1/2〉 and |±3/2〉 doublets established from static magnetic measurements.